Semiconducting and insulating oxides applied to electronic devices - Boratto, Miguel Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This work comprises the study of oxide semiconductors (Sb-doped SnO2 and TiO2) and insulating materials (ZrO2) obtained by sol-gel, and the investigation of their properties, aiming to evaluate these materials as alternative for application in electronic devices, such as Metal-Insulator-Metal (MIM) capacitors, Thin Film Transistors (TFT), and Memristors. The SnO2 thin films were obtained by two solutions with different aging times. The ZrO2 thin films were also obtained by two solutions, synthesized from two distinct methods, non-alkoxide and polymeric. The thin film deposition occurred mainly by dip- and spin-coating techniques, and the characterizations were performed through the techniques of XRD, AFM, SEM, Confocal Microscopy, EDX, RBS, TG/DSC, UV-Vis Spectroscopy, cyclic voltammetry and Impedance spectroscopy, in order to better understand the relations between the morphological and structural properties of these films and their electrical properties. The properties of Sb:SnO2 and ZrO2 thin films were analyzed in TFT and MIM devices, respectively. Alternatively TiO2 was coupled with Sb:SnO2 and applied to Memristors due to the electrical properties of this semiconductor junction. The analysis and results of the different devices investigated in this work are discussed considering their several characteristics, and it is also suggested options for possible enhancements for these devices become comparable to existent state-of-the-art devices.

Este trabalho compreende o estudo de óxidos semicondutores (Sb:SnO2 e TiO2) e isolantes (ZrO2) obtidos via sol-gel, e a investigação de suas propriedades, de modo a avaliar estes materiais como alternativa para aplicação em dispositivos eletrônicos, tais como Capacitor Metal-Isolante-Metal (MIM), transistores de filmes finos (TFT) e memristores. Os filmes finos de SnO2 foram obtidos através de duas soluções com diferentes tempos de envelhecimento. Os filmes finos de ZrO2 também foram obtidos a partir de duas soluções, produzidas por dois métodos distintos, não-alcoóxido e polimérico. A deposição dos filmes finos foi realizada por dip- e spin-coating, e as caracterizações foram realizadas através das técnicas de DRX, AFM, MEV, Microscopia Confocal, EDX, RBS, TG/DSC, Espectroscopia no espectro UV-Vis, Voltametria Cíclica e Espectroscopia de Impedância, afim de melhor compreender as relações entre propriedades morfológicas e estruturais dos filmes e suas propriedades elétricas. As características de filmes finos de Sb:SnO2 e ZrO2 foram analisadas em dispositivos TFT e MIM, respectivamente. Alternativamente, TiO2 foi acoplado ao Sb:SnO2 e juntos foram aplicados em memristores devido às propriedades elétricas da junção destes semicondutores. Os resultados das análises dos diferentes tipos de dispositivos eletrônicos investigados neste trabalho são discutidos considerando suas diversas características, e são também propostas opções de possíveis melhorias para tais dispositivos tornarem-se comparáveis aos estados-da-arte já existentes.
Semicondutores e isolantes óxidos aplicados à dispositivos eletrônicos
Keywords: Óxidos inorgânicos; SnO2; ZrO2; Dispositivos eletrônicos; Inorganic oxides; Electronic devices